PREPARATION A CASH FLOW STATEMENT AT THE MURIA COOPERATIVE, KUDUS REGENCY IN 2021 - Bernika Artamevia; Didiek Susilo Tamtomo; Zulaika Putri Rokhimah (Politeknik Negeri Semarang, 2022)
The purpose of this research is to compile and analyze cash flow reports at the Muria Cooperative Kudus Regency in 2021. The data used in the preparation of this research are secondary data, namely comparative balance sheets as of December 31, 2021 and 2020, remaining operating result for the year ended December 31, 2021, and selected data transactions in the form of a list of fixed assets in 2021 and the distribution of the remaining operating results in 2020. Data collection was obtained through interviews and documentaries. The data processing method used is description and exposition. The result of the preparation of this research is that the Cash Flow Statement at the Muria Cooperative Kudus Regency in 2021 has been prepared and in positive cash flows from operating activities and investing activities, and negative cash flows from financing activities. Muria Cooperative Kudus Regency in 2021 has a free cash flow of Rp 13.416.912, shows that the cooperative uses cash flow from operating activities to support operational needs and business development. Muria Cooperative’s cash shows good condition and is in a growing phase in business development.